Gifteringen: Tradering og praksis - Luneborg, Maria; Holm, Nora Hamnes; Døving, Runar (Tidsskrift for kulturforskning, 2024)
A wedding band is a symbol of marriage, implying a series of commitments such as loyalty, family, continuity, and household. The wedding band is an item with a long tradition, and it holds significant sentimental value, subject to a variety of unwritten rules by couples and the surrounding society. In this article, we examine the life cycle of a wedding band in Norway by exploring how it encounters the spheres of acquisition, use, and disposal. One of our main findings is that spouses adhere to a set of unwritten rules related to the use of the wedding band. In the absence of formal regulations, the popular discourse treats these informal norms as authoritative and a desirable continuity. We also find that the wedding band is an inalienable asset passed down to close female family members. The ring is attributed such great sentimental value that even when the owner passes away or goes through a divorce, the wedding band continues to endure, even when safely stored in a drawer.